การเสริมสร้างศักยภาพทางการตลาดเพื่อการพัฒนาการท่องเที่ยวอย่างยั่งยืนของชุมชนบ้านนาดี-สร้างบง ตำบลผาสุก อำเภอกุมภวาปี จังหวัดอุดรธานี - เวชชนินนาท, วัฒนจิรชัย (Area Based Development Research Journal, 2016)
บทคัดย่อไม่สมบูรณ์ Development of marketing potential to enhance the sustainable tourism of Ban Nadee-Sangbong Community. Pha Sook, Kumpawapee, Udonthani The purposes of this research were; 1) to study context and style of marketing operations 2) to create guidelines for enhancing the marketing potential and 3) to assess tourists’ opinions and satisfaction with the operation of tourist activities. The subjects in this study were 1) 17 key informants, 2) 86 samples participated in research activities, 3) 95 purposive samples joined the trial village tour, and 4) 322 Nadee-Sangbong villagers randomly selected by proportion and accidental sampling. The data were collected by the community forum, small group meeting, interview, observe activities, SWOT analysis, workshop, touring experiment, result assessment, lesson summarizing, and returning results to the community.The result showed that the community has tourism potential, but over the past years, the community did not yet launch systematically tourist activities. Therefore, tourist activities did not meet the needs of tourists. The result of creating guidelines to enhance the marketing potential was that five projects were launched to develop the marketing potential of tourist attractions in the community. developing marketing potential resulted people to be proud of, to love and to cherish their community. The result of villagers’ participation in the operation enabled the community to provide services to tourists, to conserve the beauty of environment, to create the unique souvenirs, and the effective communication of information-giving for tourists was developed. The assessment showed that the participants’ opinions on the overall operation were at an agree level ( =3.53) and tourists’ satisfaction on the overall operation were at a high level ( =4.01).